Thermal stability analysis of eccentrically stiffened Sigmoid-FGM plate with metal–ceramic–metal layers based on FSDT. Issue 1 (31st December 2016) - Hong Cong, Pham; Dinh Duc, Nguyen
Abstract: This paper researches the thermal stability of eccentrically stiffened plates made of functionally graded materials (FGM) with metal–ceramic–metal layers subjected to thermal load. The equilibrium and compatibility equations for the plates are derived by using the first-order shear deformation theory of plates, taking into account both the geometrical nonlinearity in the von Karman sense and initial geometrical imperfections with Pasternak type elastic foundations. By applying Galerkin method and using stress function, effects of material and geometrical properties, elastic foundations, temperature-dependent material properties, and stiffeners on the thermal stability of the eccentrically stiffened S-FGM plates in thermal environment are analyzed and discussed.